2010
DOI: 10.1111/j.1467-7687.2010.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a specific cross‐modal association deficit in dyslexia: an electrophysiological study of letter–speech sound processing

Abstract: The phonological deficit theory of dyslexia assumes that degraded speech sound representations might hamper the acquisition of stable letter-speech sound associations necessary for learning to read. However, there is only scarce and mainly indirect evidence for this assumed letter-speech sound association problem. The present study aimed at clarifying the nature and the role of letter-speech sound association problems in dyslexia by analysing event-related potentials (ERP) of 11-year-old dyslexic children to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
115
5
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 60 publications
8
115
5
1
Order By: Relevance
“…The MMN is evoked in an oddball paradigm when, in a sequence of auditory stimuli, a rarely presented sound (the deviant) deviates from a frequently presented sound (the standard). Typical readers showed an enhancement of the MMN in response to deviant spoken syllables compared with standards when letters were presented with the speech stimuli (Froyen, Willems, & Blomert, 2011) but not when scrambled images were presented with the speech (Mittag, Thesleff, Laasonen, & Kujala, 2013). This enhancement of the MMN was absent in children with dyslexia (Froyen et al, 2011) and adults (Mittag et al, 2013).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The MMN is evoked in an oddball paradigm when, in a sequence of auditory stimuli, a rarely presented sound (the deviant) deviates from a frequently presented sound (the standard). Typical readers showed an enhancement of the MMN in response to deviant spoken syllables compared with standards when letters were presented with the speech stimuli (Froyen, Willems, & Blomert, 2011) but not when scrambled images were presented with the speech (Mittag, Thesleff, Laasonen, & Kujala, 2013). This enhancement of the MMN was absent in children with dyslexia (Froyen et al, 2011) and adults (Mittag et al, 2013).…”
mentioning
confidence: 87%
“…This enhancement of the MMN was absent in children with dyslexia (Froyen et al, 2011) and adults (Mittag et al, 2013). The lack of enhancement of the MMN in people with dyslexia suggests that early and automatic letter-speech sound integration is absent (Froyen et al, 2011;Mittag et al, 2013).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…As mentioned before, reading impairment might reflect a deficit in audiovisual processing and, indeed, children and adult dyslexic readers have been shown to inadequately process audiovisual objects, for instance, while being presented with audiovisual and unisensory letters and speech sounds (Blau, van Atteveldt, Ekkebus, Goebel, & Blomert, 2009;Blau et al, 2010;Froyen, Willems, & Blomert, 2011;Kast, Bezzola, Jäncke, & Meyer, 2011;Kronschnabel, Brem, Maurer, & Brandeis, 2014;Mittag, Thesleff, Laasonen, & Kujala, 2013), while identifying unisensory and audiovisual speech (e.g., Hayes, Tiippana, Nicol, Sams, & Kraus, 2003), and while matching non-linguistic audiovisual materials (e.g., rectangles and tones, Widmann, Schröger, Tervaniemi, Pakarinen, & Kujala, 2012). For a subset of the sample of participants tested in this study, we have recently shown differences between dyslexic and typical adult readers in their audiovisual temporal sensitivity (Francisco, Jesse, Groen, & McQueen, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…These systems include auditory processing, multisensory integration and visual processing areas, their mutual interactions playing an important role at different stages of reading development (see review in Schlaggar and McCandliss, 2007). Neuroimaging studies of dyslexia have suggested deficits in activation of specific brain areas (e.g., Pugh et al, 2000a; Shaywitz et al, 2002; Froyen et al, 2011; Fraga González et al, 2014; Kronschnabel et al, 2014; Žarić et al, 2014) as well as in connectivity across the various brain systems for reading (Horwitz et al, 1998; Pugh et al, 2000b; Quaglino et al, 2008; van der Mark et al, 2011; Žarić et al, 2017). Studies using diffusion tensor imaging (DTI) suggested that dyslexics and typical readers may differ in the main white matter pathways that constitute the anatomical basis of the reading network (see review and meta-analysis in Vandermosten et al, 2012).…”
Section: Introductionmentioning
confidence: 99%